The Impact of Time to Rate Control of Junctional Ectopic Tachycardia After Congenital Heart Surgery. (November 2017) - Lim, Joel Kian Boon; Mok, Yee Hui; Loh, Yee Jim; Tan, Teng Hong; Lee, Jan Hau
Background: Junctional ectopic tachycardia (JET) after congenital heart disease (CHD) surgery is often self-limiting but is associated with increased risk of morbidity and mortality. Contributing factors and impact of time to achieve rate control of JET are poorly described. Methods: From January 2010 to June 2015, a retrospective, single-center cohort study was performed of children who developed JET after CHD surgery . We classified the cohort into two groups: patients who achieved rate control of JET in ≤24 hours and in >24 hours. We examined factors associated with time to rate control and compared clinical outcomes (mortality, duration of mechanical ventilation, length of intensive care unit [ICU], and hospital stay) between the two groups. Results: Our cohort included 27 children, with a median age of 3 (interquartile range: 0.7-38] months. The most common CHD lesions were ventricular septal defect (n = 10, 37%), tetralogy of Fallot (n = 7, 25.9%), and transposition of the great arteries (n = 4, 14.8%). In all, 15 (55.6%) and 12 (44.4%) patients achieved rate control of JET in ≤24 hours and >24 hours, respectively. There was a difference in median mechanical ventilation time (97 [21-145) vs 311 [100-676] hours; P = .013) and ICU stay (5.0 [2.0-8.0] vs 15.5 [5.5-32.8] days, P = .023) between the patients who achieved faster rate control than those who didn't. There was no difference in length of hospital stay and mortality between the groups. Conclusion: Our study demonstrated that time to achieve rate control of JET was associated with increased duration of mechanical ventilation and ICU stay.